Being there together social interaction in virtual environments - Schroeder, Ralph (New York ; Oxford : Oxford University Press, 2011)
This book draws together research on how people interact in virtual environments: What difference does avatar appearance make? How do avatars collaborate and play together? How do the type of system and the space affect how people engage with each other? How does interaction between avatars differ from face-to-face interaction?
Description based on print version record.
Includes bibliographical references and index.
Keywords: Social interaction; Shared virtual environments